Evolution of liver donation in Moscow. Movement towards expanded donor selection criteria - M. G. Minina; D. V. Voronov; E. A. Tenchurina (Вестник трансплантологии и искусственных органов)
The objective of the study was to investigate the evolution and trends in liver donation in the city of Moscow, with special focus on the expansion of liver donor selection criteria for transplantation. Materials and methods. The study included 1,548 effective donors (EDs) in the period from January 1, 2012 to December 31, 2020. Their basic characteristics – age and cause of death – are presented. The dynamics of changes in the age groups of donors and the dynamics of the number of ≥60-year-old liver donors were studied. The influence of expanded liver donor selection criteria over the dynamics of the number of transplant surgeries and patient flow on the waiting list was assessed. Results. During the study period, the number of effective liver donors (ELDs) in Moscow increased 4.7-fold. The average age of ELDs increased from 37.1 in 2012 to 48.8 in 2020. There was an absolute prevalence of donors who died from cerebrovascular accident compared with donors who died from traumatic causes, 83.4% vs 16.6%, respectively. Since 2016, there has been a progressive increase in ≥60-year-old liver donors; the number of such donors in 2020 reached 39, accounting for 13.6% of the total pool of EDs. The progressive growth in the number of liver transplants has significantly influenced patient movement on the waiting list. In 2012, there was a 25.2% increase in the number of liver transplants per 100 patients on the waiting list; by 2020, it had reached 86.6%. Conclusion. The results reasonably indicate an increase in liver donation and liver transplantation (LTx) in Moscow. Comparison of Russian data with those of leading foreign donor programs shows that the trends in the donor pool in the context of older age, including ≥60-year-old donors, and shifting causes of donor death towards cerebrovascular diseases are similar. An overall increase in donor activity and expansion of liver donor criteria contributed to an increase in the number of transplants performed per 100 patients on the waiting list, which, in turn, reduced the waiting time for a donor organ and increased the intensity of patient flow on the waiting list.